Optimizing the Role of the BUM Desa in the Development of Rural Economy During the COVID-19 Pandemic - Zakariya, Rizki (Universitas Negeri Semarang, 2020)
The Covid-19 Pandemic had a negative impact on the socio-economic activities of the community in the village. The purpose of this study is to describe the urgency of optimizing the role of BUM Desa in developing rural economies in the midst of the Covid-19 Pandemic and solutions for this optimization. While the research method used is descriptive qualitative with a case approach and a statutory approach. The results of this study indicate the urgency of optimizing the role of BUM Desa in developing rural economies in the midst of the Covid-19 Pandemic because of the large contribution of BUM Desa to the national economy. However, the existence of Covid-19 caused economic losses for rural communities. Therefore, efforts to optimize the role of BUM Desa include encouraging BUM Desa as a provider of staple foodstuffs in the village, cooperation of BUM Desa with various parties, providing incentives and working capital credit for Village BUM, and conducting education and training for Village BUM managers.